Analysis Of The Amount Of Leachate Pollution On The Environmental Health Of Settlements At Bakung Final Disposal Site Bandar Lampung City - Lenty Hoya, Ade; Kamelia, Marlina; Sari, Irma (Sean Institute, 2023)
Leachate is residual waste that is exposed to water when it rains. Leachate contains physical, chemical and biological parameters that are dangerous if it enters the canals and residential areas of residents. Many problems will arise if the leachate is not treated and left alone. The purpose of this study was to determine the amount of leachate pollution on the environmental health of settlements at the Bakung final disposal site in Bandar Lampung. This type of research is qualitative research and is presented descriptively. The test sample was taken using the composite sample method (combined place) at three pool points, each of 1.7 liters with a total of 5 liters and homogenized. Samples were analyzed using SNI 8995:2021 and the water quality was assessed using the Pollution Index (IP) method. To find out the health of the environment using interviews with the community around the final disposal site. The results of the analysis showed that the physical and chemical parameters of leachate at Bakung landfill that exceeded the leachate quality standards were TSS (538.33 mg/L), BOD (5382 mg/L), COD (8220 mg/L), Total Nitrogen (91 mg/L). If the leachate is only collected without further treatment, it will result in the leachate entering residential canals and contaminating the well water in the surrounding area and possibly causing health problems such as skin irritation. Toxic environment, water unfit for consumption evenblue baby syndrome in infants and an increased risk of colon cancer.